Wellness in Physician Assistant Education: Exploring Mindfulness, Well-Being, and Stress. Issue 2 (June 2022) - Hoover, Eve B.; Butaney, Bhupin; LeLacheur, Susan; Straker, Howard; Bernard, Kari; Coplan, Bettie; Carr, Candra; Blesse-Hampton, Laura; Naidu, Amee
Abstract : Purpose: The current study examined stress reduction activities most commonly used by matriculating physician assistant (PA) students to better understand how students are approaching self-care and management of stress. In particular, the study examined levels of mindfulness and well-being to understand how these relate to various stress reduction approaches at the time of matriculation. Methods: Newly matriculated students at 9 PA programs located across the nation were surveyed (n = 294). Validated survey instruments assessed levels of mindfulness and general well-being. Stress reduction activities were also assessed. Univariate and multivariate analyses were used to examine levels of mindfulness and levels of well-being to see how these relate to various stress reduction approaches. Results: The survey response rate was 72%. Nearly one-third of respondents (32%) identified meditation as one of their stress reduction activities, and more than half (53%) reported having participated in mindfulness practice at least once in the past year. Sixty-four percent of students reported awareness of mindfulness practices, while only 16% reported frequent practice within the year prior to matriculation. When looking at variables of interest, decentering and psychological flexibility were significant in accounting for student-reported perceived stress and life satisfaction. Conclusion: PA students are likely receptive to mindfulness-based interventions that have the potential to improve well-being and reduce stress. There is opportunity for programs to incorporate reliable and structured training within curricula that effectively increases levels of mindfulness and, in doing so, can lead to improvement in perceived stress and life satisfaction. Further research may assist educators in the development of strategies to promote student and clinician wellness.